2023
DOI: 10.1212/wnl.0000000000207675
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Biomarkers of Alzheimer Disease With Cognition and Medical Comorbidities in a Biracial Cohort

Vijay K. Ramanan,
Jonathan Graff-Radford,
Jeremy Syrjanen
et al.

Abstract: Background and Objectives:Recent advances in blood-based biomarkers offer the potential to revolutionize diagnosis and management of Alzheimer’s disease (AD), but additional research in diverse populations is critical. We assessed the profiles of blood-based AD biomarkers and their relationships to cognition and common medical comorbidities in a biracial cohort.Methods:Participants were evaluated through the Mayo Clinic Jacksonville Alzheimer’s Disease Research Center and matched on age, sex, and cognitive sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…On the other hand, our ndings in AD patients align with prior research, indicating a stronger correlation between cognitive measures and tau markers when compared to Aβ1-42 in AD 28, 29 . In a recent study by Ramanan et al 2023 involving a large cohort of patients with AD, no association was found between the Aβ 42/40 ratio and MMSE scores in the overall sample, whereas p-tau 181 levels exhibited a positive association with MMSE scores 30 . The lack of signi cant ndings in our study and previous studies related to Aβ1-42 levels and cognition in patients with AD can be attributed to a hypothesis proposing that amyloid load remains relatively stable in the brain throughout various clinical phases of AD and does not exhibit substantial changes as the disease progresses to more severe stages 31 .…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, our ndings in AD patients align with prior research, indicating a stronger correlation between cognitive measures and tau markers when compared to Aβ1-42 in AD 28, 29 . In a recent study by Ramanan et al 2023 involving a large cohort of patients with AD, no association was found between the Aβ 42/40 ratio and MMSE scores in the overall sample, whereas p-tau 181 levels exhibited a positive association with MMSE scores 30 . The lack of signi cant ndings in our study and previous studies related to Aβ1-42 levels and cognition in patients with AD can be attributed to a hypothesis proposing that amyloid load remains relatively stable in the brain throughout various clinical phases of AD and does not exhibit substantial changes as the disease progresses to more severe stages 31 .…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, our ndings in AD patients align with prior research, indicating a stronger correlation between cognitive measures and tau markers when compared to Aβ1-42 in AD 28,29 . In a recent study by Ramanan et al 2023 involving a large cohort of patients with AD, no association was found between the Aβ 42/40 ratio and MMSE scores in the overall sample, whereas p-tau 181 levels exhibited a positive association with MMSE scores 30 . The lack of signi cant ndings in our study and previous studies related to Aβ1-42 levels and cognition in patients with AD can be attributed to a hypothesis proposing that amyloid load remains relatively stable in the brain throughout various clinical phases of AD and does not exhibit substantial changes as the disease progresses to more severe stages 31 .…”
Section: Discussionmentioning
confidence: 90%
“…Also, participants of this community‐based cohort were predominantly white. Prior studies examining performance of BBBs in racial and ethnic diverse groups have been conflicting 31 , 32 , 33 , 34 and more data are needed to determine if the diagnostic performance observed in this study is applicable to more diverse populations. Finally, we used amyloid‐PET as the outcome measure; therefore, studies examining performance of BBBs using CSF biomarkers to characterize amyloid pathology may not be directly comparable as CSF markers can also have varying performance for detecting an abnormal amyloid‐PET.…”
Section: Discussionmentioning
confidence: 94%